The Effectiveness of Varying Combination Ratios of A. cordifolia and M. indica against Field and Laboratory Strains of P. falciparum In Vitro - Yakubu Jibira; Elizabeth Cudjoe; Frederick M. Tei-Maya; Benjamin Ayensu; Linda E. Amoah (Journal of Parasitology Research)
Background. Drug resistance in malaria is a global problem, with reports of Plasmodium parasites resistant to the current first-line antimalarial drug, artemisinin, expanding from Southeast Asia to Africa. There is therefore an urgent need to identify new drug candidates that will be effective against the existing malaria parasites. Drug combination therapy presents a myriad of advantages over monotherapy including delayed onset of resistance, potentiation, and synergism. This present study explored the effectiveness of combinations of aqueous extracts of Alchornea cordifolia (A. cordifolia) and Mangifera indica (M. indica) at clearing both laboratory and field isolates of P. falciparum. Methods. Synchronized ring stage cultures of field (FA08) and laboratory strains (NF54 and CamWT_C580Y) of P. falciparum were subjected to combinations of different concentrations and ratios of aqueous extracts of A. cordifolia and M. indica. The growth inhibition of the individual plant extracts and their combinatory effects were studied in vitro using SYBR Green I drug assay. Results. The A. cordifolia extract exhibited 50% inhibitory concentration (IC50) of 2.71, 7.80, and 3.56 μg/mL against the NF54, CamWT_C580Y, and FA08 parasite strains, respectively. Mangifera indica exhibited IC50 of 18.11, 20.08, and 10.23 μg/mL against the NF54, CamWT_C580Y, and FA08 parasite strains, respectively. Additive, synergistic and antagonistic interactions were observed at different combinations of A. cordifolia and M. indica extracts. Conclusion. A combination product containing A. cordifolia and M. indica has the potential to serve as an effective antimalarial as majority of the tested combinations of aqueous extracts of A. cordifolia and M. indica extracts exhibited synergistic effects in vitro against the NF54, CamWT_C580Y, and FA08 P. falciparum strains.